2015
DOI: 10.14738/assrj.24.1061
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Gender and Their Job Satisfaction with Service Delivery in Federal Universities in South Nigeria

Abstract: An) investigation) into) the) gender) determination) of) students') satisfaction) with) service) delivery) in) federal) Universities) in) southTsouth) geopolitical) zone) of) Nigeria) was) the) subject) of) this) study.) To) execute) the) study,) the) hypothesis) was) formulated) and) literature)reviewed.)Using)the)stratified)random)sampling)technique)1,700)students)out) of)a)population)of)70,808)formed)the)study's)sample.)They)were)Years)One,)Two,)Three,) and) Four) regular) undergraduate) students) of) the) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Contrary to this study's finding, gender was shown by a study to have a substantial effect on the usage of ICT tools for record management, teaching and research (Odigwe & Owan, 2020). Another research documented that there are large disparities between males and females in their satisfaction with the provision of university resources (Akpoiroro & Okon, 2015). The outcomes of these reports and the outcomes of the present research differed due to the variations in the dependent variable tested, as well as the level of education in question.…”
Section: Discussion Of Findingscontrasting
confidence: 54%
See 1 more Smart Citation
“…Contrary to this study's finding, gender was shown by a study to have a substantial effect on the usage of ICT tools for record management, teaching and research (Odigwe & Owan, 2020). Another research documented that there are large disparities between males and females in their satisfaction with the provision of university resources (Akpoiroro & Okon, 2015). The outcomes of these reports and the outcomes of the present research differed due to the variations in the dependent variable tested, as well as the level of education in question.…”
Section: Discussion Of Findingscontrasting
confidence: 54%
“…Studies have shown differences in students' satisfaction with the quality of service delivery, based on gender. For example, a study revealed substantial gaps between male and female students in their satisfaction with the delivery of university services such as educational, library, medical, travel, defense, hostel and ICT services (Akpoiroro & Okon, 2015). Similarly, proof from yet another study showed that there is a large disparity in student satisfaction across gender; these differences arise in terms of student-instructor engagement, student support and facility oversight (Daniel et al, 2017).…”
Section: Gender and Students' Satisfaction With The Study Of Ictmentioning
confidence: 99%